MASYARAKAT PERBATASAN RI-MALAYSIA DAN KASUS ASKAR WATANIAH: RELEVANSI PERUBAHAN KEBIJAKAN KESEJAHTERAAN - Zainuddin Djafar (LIPI Press, 2008)
This writing seeks to determine the extent of the welfare factor as a basis of the decision taken by Indonesians living in Malaysian border to join the Malaysian Askar Wataniah paramilitary unit. The case itself signifies how government welfare plannings have yet to be realized in its fullest capacity to prevent citizens from considering the alternative to join a foreign security. This is among others, due to cronic economic and development retardness faced by the region. In light of such circumstances, better concepts and policies concerning welfare in this region must be developed, especially through policy analyses and recommendations, which would contribute towards preventing the recurrence of similar cases. The case has become more serious having in mind the different development of Indonesia with its neighbors, in terms of poverty, deprafity, educational backwardness, retardness, and marginality (Five K) remains to be a dominant feature in many Indonesian border societies. Therefore, developments of new economic growth hubs has become an ever essential priority in the crusade to combat the Five K, especially through the development of better trade infrastructures in the border areas, in order to improve border tradings and its positive effects to the society. Government intervention in such project will also need to reach the Political, Socio-Cultural, and Defence-Security dimensions of the issue in order to anticipate problems such as the low human resources quality in the region, etc. Thereby, the following policy stages may need to be considered; (A) to increase within the interaction between the government and the border societies, (B) to empower border societal participation, (C), to raise a consciousness towards the development of human and natural resources for the benefit of all elements of the border societies.